Tissue Factor Encryption/de-encryption Is not Altered in the Absence of the Cytoplasmic Domain - Carson, Steven D.; Bromberg, Michael E. (Thrombosis and Haemostasis, 2000)
Since the cytoplasmic domain of tissue factor (TF) appears to have a role in TF function beyond coagulation, experiments were conducted to determine whether the cytoplasmic domain also has a role in regulating procoagulant activity of TF present in the cell membrane. TF encryption was quantitated in human YU-SIT1, U87-MG, and mouse 3T3 cells which were transfected for expression of human tissue factor or a construct lacking the cytoplasmic domain (TFCD). Comparison of intact cells (encrypted) with fully disrupted cells (de-encrypted) showed that TF and TFCD were equally encrypted with respect to function in fX activation. Moreover, cells expressing TF and TFCD were indistinguishable in their procoagulant responses to A23187-calcium and varied concentrations of nonionic detergents. TF in membrane vesicles spontaneously shed by U87-MG cells was largely, but incompletely, de-encrypted, and the degree of de-encryption was independent of the cytoplasmic domain. We conclude that the predominant mechanism(s) for encrypting TF procoagulant activity is independent of the cytoplasmic domain.
Keywords: Tissue factor; encryption; cytoplasmic domain